Balance and preference in activity participation for informal caregivers of people with aphasia: A questionnaire study. Issue 9 (1st September 2020) - Haley, Katarina L.; Jacks, Adam; Morrison, Blaise; Richardson, Jessica D.
ABSTRACT: Background: With increased attention to third-party disability, there is a need to evaluate how informal caregivers of people with aphasia participate in diverse life activities. Qualitative research has improved our understanding of experiences and priorities in this essential group of stakeholders. However, there has been limited effort to confirm results quantitatively and based on robust sample sizes. Aims: To characterize the balance and preference among home/work, leisure, and social activities for informal caregivers based on questionnaires that can also be used with people who have aphasia. Methods & Procedures: Seventy caregivers for people with aphasia and 46 control participants who were not caregivers completed the Community Integration Questionnaire (CIQ) and a questionnaire version of the Life Interests and Values (LIV) Cards. Outcomes & Results: CIQ scores did not differ statistically between groups, but the frequency of endorsed activities on the LIV Cards did. Whereas current engagement in home and community activities was similar for the two groups, caregivers reported doing significantly fewer activities in social, physical, and creative and relaxing categories. In contrast to the balance difference for their current life, participants in both groups agreed about wanting to do more social and leisure activities, with many activities rising to the top in both groups. Conclusions: Informal caregivers for people with aphasia experience a measurable difference between activities they currently do in their lives and activities they want to do. With modification, interviews and questionnaires intended for people with disability can provide a caregiver perspective on living with aphasia that may facilitate coordinated and relationship-focused intervention.